Metodologias de inoculação e detecção de Fusarium oxysporum f. sp. vasinfectum em sementes do algodoeiro (Gossypium hirsutum L.) - Sousa, Marcella Viana de (2006)
Cotton wilt, caused by Fusarium oxysporum f.sp. vasinfectum (Atk.) Snyder & Hansen, is one of the most important diseases of this crop. To study the seed-borne implications of that fungus, it is important to make available infected seeds at various levels. Having that in sight, the objectives of this study were: i) to evaluate the effectiveness of inoculation procedures and periods of exposition of cotton seeds to Fusarium oxysporum f. sp. vasinfectum, through water restriction technique and ii) to establish a reliable and a simple methodology of detection of Fusarium oxysporum f. sp. vasinfectum in cotton seeds for routine seed health analysis. The following methods were compared: 1. seed immersion in a conidial suspension for 10 min followed by incubation in a paper substrate with an osmotic potential of -1.0 Mpa, 2. atomization of a conidial suspension upon the substrate and on the seeds, arranged in single layers, and 3. direct contact of the seeds with the fungal mycelium developed on a paper substrate. All methods were able to provide seeds with different inoculum potential, equivalent to different exposition times, 24, 48, 72, 96 and 120 h, of seeds to the fungus. To evaluate the infection efficacy, germination tests on roll paper and in soil/sand substrate and health tests were applied. The most effective method was the immersion of seeds in inoculum suspension plus incubation in substrate with water restriction. The maximum period of time that seeds remain in contact with the pathogen, without affecting their physiological quality was 50 h. Higher infection levels were obtained with longer period of seed exposition to the fungus. With regard to the detection methodology, six substrates were compared: 1. 2,4-D (sodium salt), 2. PDA, 3. PDA + iprodione, 4. DG-18, 5. quintozene and 6. cotton seed extract, all dissolved in diluted agar. Considering the incidence and typical purple colour of F. oxysporum mycelium and the inhibition of contaminant fungi, it was found that the most adequate substrate was filter paper moistened with quintozene dissolved in a diluted agar medium under incubation conditions recommended for testing cotton seeds.